1991
DOI: 10.1093/bja/67.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flumazenil on Cerebral Blood Flow and Oxygen Consumption After Midazolam Anaesthesia for Craniotomy

Abstract: Cerebral blood flow (CBF) and cerebral metabolic rate for oxygen (CMRO2) were measured by a modification of the Kety-Schmidt technique using i.v. xenon-133 in 20 patients undergoing craniotomy for supratentorial cerebral tumours. Anaesthesia was induced and maintained with midazolam, fentanyl and nitrous oxide. Pancuronium was given for neuromuscular block. The lungs were ventilated to normocapnia. The first flow measurements were performed approximately 1 h after induction of anaesthesia. At the end of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In contrast, Knudsen et al. demonstrated that flumazenil had no effect on CBF and CMRO 2 when used for reversal of midazolam anesthesia for craniotomy (144).…”
mentioning
confidence: 99%
“…In contrast, Knudsen et al. demonstrated that flumazenil had no effect on CBF and CMRO 2 when used for reversal of midazolam anesthesia for craniotomy (144).…”
mentioning
confidence: 99%
“…However, the present observation of a further reduction in MCBFV after flumazenil administration was inconsistent with previous studies that reported restoration or no changes in steady-state CBF after flumazenil administration. 3,4 The present results suggest for the first time that, despite complete antagonism of the sedative effects of midazolam, flumazenil administration does not antagonize both the decreases in steady-state CBF and alterations in dynamic cerebral autoregulation induced by midazolam. The present study also attempted to reveal the effects on cerebral circulation of flumazenil alone without midazolam sedation.…”
Section: Discussionmentioning
confidence: 54%
“…14,15 However, the antagonistic effects on CBF of flumazenil administered after midazolam are controversial. 3,4 As mentioned in the introduction, this discrepancy between previous studies may be explained by the differences in the level of sedation/awareness and/or the sequence of administration of the 2 drugs. Therefore, the present study investigated the changes in steady-state MCBFV after midazolam sedation followed by flumazenil administration, with assessment of sedation/awareness levels.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations